Unification of the Globally Distributed Spindle-Shaped Viruses of the Archaea - Krupovic, Mart (American Society for Microbiology, 2014)
Viruses with spindle-shaped virions are abundant in diverse environments. Over the years, such viruses have been isolated from a wide range of archaeal hosts. Evolutionary relationships between them remained enigmatic, however. Here, using structural proteins as markers, we define familial ties among these “dark horses” of the virosphere and segregate all spindle-shaped viruses into two distinct evolutionary lineages, corresponding to Bicaudaviridae and Fuselloviridae. Our results illuminate the utility of structure-based virus classification and bring additional order to the virosphere.